New Binary Code Combined with New Chaotic Map and Gold Code to Ameliorate the Quality of the Transmission - Mohamed Krim; Adda Ali-Pacha; Naima Hadj-Said (Indonesian Journal of Electrical Engineering and Computer Science, 2017)
While the private radio communications field has grown in recent years, the communication method known as spread spectrum name has gained much prominence. A spread spectrum method can be combined with multiple access method CDMA for dividing sequences to create multi-user communication systems with very good performance of interference between symbols.The production of the chaotic sequence in scanning system and the information system according to DS-CDMA remains a hot research problem in this study to supervise in the knowledge wireless communication. This fact is still a question in establishing the secret code random spread sequence between the transmitter and the receiver.In DS-SS’s spreading is important to embed security information.It can avoid many problems in the complex calculation of the true circle. Furthermore the pseudo chaotic is reconstructed in the conventional gold to change shape with the logical operator “XOR” the results in simulation result shows in progress.It improves also the computing speed as this can solve the new equation of the problem in the original logistic map.There certainly has a kind in design: spreading chaotic sequence, chaos with gold code; including the number of users.So these are less in number and also limit the security and to can improve the ameliorate the quality of the transmissionand performance in terms of allowable number of users.The Bit error rate (BER) performance of the system is evaluated in multi-user environment under AWGN and reveals that the DS-SS system using new binary code combined with new logistic mapand gold code to ameliorate the quality of the transmission.